Elizabethkingia Meningoseptica: An Emerging Pathogen Causing Neonatal Meningitis. A Case Report - Vishnu K P; Bindu A; Dhanya; Purushothaman (Asian Journal of Clinical Pediatrics and Neonatology, 2023)
Elizabethkingia meningoseptica is a non-fermentative gram-negative bacillus ubiquitously found in hospital environment and commonly resistant to multiple antibiotics. Early diagnosis and institution of antibiotic therapy for appropriate duration is essential. We report two cases of bacteremia of Elizabethkingia. meningoseptica treated successfully with antibiotics and supportive meassures.